Synthesis of N-Sulfonylazetidin-2-imines via the Copper(I) Oxide Catalyzed Multicomponent Reaction of Alkynes, Sulfonyl Azides and Diimines under Solvent-Free Conditions - Yi, Xiaohu; Barry, Badru-Deen; Liao, Peiqiu; Bi, Xihe (Synthesis, 2012)
N-Sulfonylazetidin-2-imines are synthesized efficiently via three-component reactions of sulfonyl azides, terminal alkynes, and carbodiimides using copper(I) oxide as an inexpensive and eco-friendly catalyst under solvent-free conditions, without the need for an additional base or ligand. The same method is applied to the preparation of an azetidin-2-ylidene derivative using a 1,2-diimine as the nucleophile.
Keywords: N-sulfonylazetidin-2-imines; multicomponent reaction; copper(I) oxide; solvent-free; sulfonyl azides